Bone repair material based on pH controlled release and preparation method thereof

By using pH controlled release technology and 3D printing technology in bone repair materials, the crisscrossing composite bone repair scaffolds are solved, and the problem that existing bone repair materials cannot effectively control the decomposition rate is achieved, the continuous quantitative release of magnesium ions and bone tissue repair is achieved, which improves bone repair performance and reduces the number of surgeries.

CN119733111APending Publication Date: 2025-04-01CHINA UNIV OF MINING & TECH +1

Patent Information

Application Number
CN202411624767.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing bone repair materials cannot effectively control the rate during the disassembly and release process, and cannot match the repair of the patient's bone defects, which in turn cannot effectively promote bone tissue repair.

Method used

Using a bone repair material based on pH controlled release, crisscrossed composite bone repair scaffolds are printed through 3D printing technology. The combination of polycaprolactone, nanohydroxyapatite and nanomagnesium oxide is used to control the fractional release rate according to the pH value to achieve continuous quantitative release of magnesium ions.

Benefits of technology

The slow degradation of bone repair materials in the human body is achieved. The released magnesium ions can promote bone tissue repair and accelerate the release of magnesium ions in the inflammatory environment, playing an anti-inflammatory role, reducing the need for secondary surgery and improving bone repair performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733111A_ABST
    Figure CN119733111A_ABST
Patent Text Reader

Abstract

The invention discloses a bone repair material based on pH controlled release and a preparation method thereof. The bone repair material comprises the following raw materials: polycaprolactone, nano hydroxyapatite and nano magnesium oxide. The composite bone repair scaffold has the beneficial effects that the composite bone repair scaffold with excellent biocompatibility, excellent osteogenesis performance, excellent degradation performance and pH controlled release of magnesium ions is prepared by printing the bone repair material through a 3D printing technology, a temporary three-dimensional structure can be provided for cells, cell adhesion, proliferation and differentiation are promoted, growth factors are released at the same time, and the growth rate of the cells is increased. The formation of new bone tissues is guided; the composite bone repair scaffold can continuously and quantitatively release magnesium ions through pH value control, when osteoarthritis or bone tissue inflammation occurs at a bone defect part due to improper operation and rejection reaction, the magnesium ion release speed of the composite bone repair scaffold is increased, the anti-inflammatory effect is achieved, and the magnesium ions which are continuously released can promote bone tissue repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a bone repair material, in particular to a bone repair material based on pH controlled release and a preparation method thereof, belonging to the technical field of biomedical materials. Background Art

[0002] Bone repair scaffolds, also known as bone scaffolds or bone repair materials, are an important technology in the field of biomedical engineering, mainly used to promote fracture healing, bone defect repair and bone tissue regeneration. 2.2 million bone transplants are performed worldwide each year, increasing at a rate of 13% per year. Fractures and bone defects are common clinical problems. Although traditional treatments such as autologous bone transplants, allogeneic bone transplants and synthetic bone substitutes can solve the problem to a certain extent, they have many limitations, such as insufficient donors, immune rejection and biocompatibility issues. In order to overcome these limitations, bone repair scaffolds have emerged as a new type of treatment. Bone repair scaffolds are usually made of biocompatible and biodegradable materials. They can provide cells with a temporary three-dimensional structure, promote cell adhesion, proliferation and differentiation, and release growth factors to guide the formation of new bone tissue.

[0003] Traditional orthopedic clinical implants are made of non-degradable metals. These metals include stainless steel, titanium alloys, and cobalt-chromium alloys. Although they are widely used clinically, they also have important limitations, such as stress shielding effects, which lead to the fragility of surrounding bone tissue and susceptibility to secondary fractures. There are pros and cons in clinical treatment; and traditional materials are non-degradable. If a secondary operation is performed due to the need to remove internal fixation or other requirements, it will greatly increase the cost of treatment and bring additional pain to patients. In addition to traditional metal orthopedic clinical implants, another commonly used method in clinical practice is autologous transplantation or allogeneic transplantation. Autologous bone grafts are taken from the patient's own body and are still the "gold standard" graft choice, but the supply is limited and leads to high morbidity in patients. Xenograft bone is an attractive alternative from donors with controlled biology, with a large supply and theoretically low cost, but there may be rejection, and the clinical results of orthopedic applications are mixed.

[0004] In the prior art, there is a bone repair material, a preparation method of the bone repair material, and an application thereof disclosed in publication number CN113694254A. The preparation method of the bone repair material provided by the present disclosure utilizes the self-organization of hydroxyapatite particles and collagen to uniformly wrap the hydroxyapatite particles inside the three-dimensional network of collagen fibers to prepare a bone repair material having a porous structure and plasticity. However, although the bone repair material prepared by the prior art can be decomposed and released in the patient's body, the rate of decomposition and release cannot be well controlled during the decomposition process, that is, it cannot match the repair condition of the patient's bone defect, and thus cannot promote bone tissue repair well. Summary of the invention

[0005] The purpose of the present invention is to provide a bone repair material based on pH controlled release and a preparation method thereof in order to solve at least one of the above technical problems.

[0006] The present invention achieves the above-mentioned purpose through the following technical scheme: a bone repair material based on pH controlled release, comprising raw materials constituting the bone repair material including polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide, wherein the raw materials of the bone repair material are calculated by weight: polycaprolactone is 5-10 parts, nano-hydroxyapatite is 5-10 parts, and nano-magnesium oxide is 40-80 parts; The bone repair material uses 3D printing technology to print a criss-cross composite bone repair scaffold, and the composite bone repair scaffold controls the decomposition and release rate based on the pH value.

[0007] As a further solution of the present invention: the composite bone repair scaffold prepared by printing the bone repair material continuously degrades in the human body, and the degradation products of the composite bone repair scaffold include water, carbon dioxide and hydroxyapatite.

[0008] As a further embodiment of the present invention, the hydroxyapatite is partially degraded, and calcium ions are released when the hydroxyapatite is degraded.

[0009] As a further solution of the present invention: during the degradation process of the composite bone repair scaffold, the decomposition of polycaprolactone is divided into two stages: First, polycaprolactone undergoes hydrolysis and cleavage of ester bonds in the human body, causing its molecular weight to gradually decrease, but at this stage, its quality does not decrease significantly; Secondly, when the molecular weight drops below 5000, the material breaks down into fragments and begins to lose weight; at the same time, most of the degradation products of polycaprolactone are absorbed and digested by human cells, while the parts that cannot be absorbed are excreted from the body through the excretory system.

[0010] As a further solution of the present invention: during the degradation process of the composite bone repair scaffold, the degradation rate of nano-magnesium oxide is affected by the pH value. Under different pH conditions, the solubility and reactivity of nano-magnesium oxide are different: Under acidic conditions, the solubility of nano-magnesium oxide increases because nano-magnesium oxide reacts with hydrogen ions to generate magnesium ions and water; this reaction promotes the degradation of nano-magnesium oxide because the surface of nano-magnesium oxide is corroded by acidic substances, accelerating its dissolution process; During the degradation process of polycaprolactone, carbon dioxide and water are produced, and further reaction will generate carbonic acid, thereby slightly reducing the pH value of the bone defect. The reduced pH value will accelerate the hydrolysis of nano-magnesium oxide, further accelerating the release of magnesium ions in the bone defect.

[0011] As a further solution of the present invention: magnesium ions generated by degradation of nano-magnesium oxide activate the PI3K / Akt signaling pathway in mammalian cells.

[0012] As a further solution of the present invention: the bone repair material can also prevent and control orthopedic inflammation.

[0013] A method for preparing a bone repair material based on pH controlled release, the method for preparing the bone repair material comprising the following steps: S1. Mixing bone repair materials by melting method: adding quantitatively weighed polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide into a polytetrafluoroethylene beaker, heating and dissolving the composite material in an oil bath, and setting the temperature of the oil bath to 150-160°C; S2. After melting for 30 to 40 minutes, take out the polytetrafluoroethylene beaker, stir the materials with a polytetrafluoroethylene stirring rod to fully mix them, stir for 5 to 10 minutes, and then heat them in an oil bath again. Repeat the above steps 4 to 6 times. After multiple melting and stirring, polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide are fully mixed. S3. Fill the evenly mixed composite bone repair material into a barrel, install the barrel into a pneumatic fused deposition biological 3D printer, and use the biological 3D printer to print a criss-cross composite bone repair scaffold.

[0014] The beneficial effects of the present invention are as follows: the raw materials of the bone repair material disclosed in the present invention include polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide, and the bone repair material is printed by 3D printing technology to prepare a composite bone repair scaffold with excellent biocompatibility, excellent osteogenesis, excellent degradation performance, and pH-controlled release of magnesium ions. The composite bone repair scaffold can provide cells with a temporary three-dimensional structure, promote cell adhesion, proliferation and differentiation, and release growth factors to guide the formation of new bone tissue; The composite bone repair scaffold disclosed in the present invention can release magnesium ions continuously and quantitatively by controlling the pH value. When osteoarthritis or bone tissue inflammation occurs at the bone defect site due to improper surgery or rejection reaction, the composite bone repair scaffold releases magnesium ions faster, playing an anti-inflammatory role, and the continuously released magnesium ions can promote bone tissue repair. The composite bone repair scaffold disclosed in the present invention will slowly degrade after being implanted in the human body. When the bone tissue is fully grown, the composite bone repair scaffold will also be almost completely degraded, and the degradation product is hydroxyapatite that originally exists in the human skeleton. No secondary surgery is required, which reduces the pain of the patient, and has better bone repair performance than traditional bone repair scaffolds. The bone repair material disclosed in the present invention can increase the concentration and speed of magnesium ion release when inflammation occurs at the bone defect site. The increased magnesium ion concentration changes the acidic environment of inflammation to a normal pH level, thereby inhibiting inflammation and playing an anti-inflammatory role. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of the principle of releasing magnesium ions from the bone repair material of the present invention; Figure 2 It is a schematic diagram of the tensile test of the present invention; Figure 3 It is a schematic diagram of the compression test of the present invention; Figure 4 This is a schematic diagram of a compression cycle test of the present invention; Figure 5 This is a schematic diagram of the tensile fracture sample of the present invention; Figure 6 This is a schematic diagram of the surface microscopic morphology of the composite material bone repair scaffold of the present invention; Figure 7 This is a schematic diagram of the cross-sectional microscopic morphology of the composite material bone repair scaffold of the present invention; Figure 8 This is a schematic diagram of the degradation experiment of the composite material bone repair scaffold of the present invention; Fig. 9 This is a schematic diagram of the magnesium ion release curve of the composite material bone repair scaffold of the present invention; Fig.10 This is a schematic diagram of the magnesium ion release curve of the composite material bone repair scaffold of the present invention in an inflammatory environment; Fig.11 This is a schematic diagram of the mineralization experiment of the bone repair scaffold of the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Embodiment 1, a bone repair material based on pH controlled release, comprising raw materials constituting the bone repair material including polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide, wherein the raw materials of the bone repair material are measured in parts by weight: polycaprolactone is 5-10 parts, nano-hydroxyapatite is 5-10 parts, and nano-magnesium oxide is 40-80 parts; The bone repair material uses 3D printing technology to print a composite bone repair scaffold with a criss-cross three-dimensional network structure. The composite bone repair scaffold controls the decomposition and release rate based on the pH value. The composite bone repair scaffold can provide good mechanical support for the bone defect site and protect the original bone tissue structure when the new bone has not yet fully grown.

[0018] Embodiment 2: In addition to all the technical features of Embodiment 1, this embodiment also includes: like Figure 1 As shown, the composite bone repair scaffold prepared by printing the bone repair material continues to degrade in the human body, and the degradation products of the composite bone repair scaffold include water, carbon dioxide and hydroxyapatite. As the bone tissue is repaired, the composite bone repair scaffold gradually degrades and disappears. The water and carbon dioxide produced by degradation are harmless to the human body. The hydroxyapatite produced by degradation is the original material in the human bone tissue and can be used to enhance the mechanical properties of the bone tissue.

[0019] like Figure 2 and Figure 3 As shown in the figure, the mechanical properties of the composite bone repair scaffold were tested using a universal testing machine. The tensile properties of the polycaprolactone bone repair scaffold are poor, mainly because the polycaprolactone material has excellent ductility. During the tensile test, the polycaprolactone scaffold was stretched and deformed layer by layer, but the maximum tensile strength was low. After adding nano-hydroxyapatite, the maximum tensile strength increased by 300%. After continuing to add nano-magnesium oxide, the maximum tensile strength increased by 600% compared with polycaprolactone. From the compression test, the compressive strength of the bone repair scaffold increased significantly after adding nano-hydroxyapatite and nano-magnesium oxide, which increased by 129% and 214% respectively compared with the polycaprolactone scaffold, which is sufficient to meet the support strength requirements of the bone defect site in the human body.

[0020] like Figure 4As shown, the composite bone repair scaffold was subjected to compression cycle test. The results show that the composite bone repair scaffold disclosed in the present invention has a similar energy loss each time under five cycles of compression, has stable compression performance, has the ability to withstand repeated pressure, and meets the requirement that the human body is often subjected to repeated compression.

[0021] like Figure 5 As shown in the figure, the fracture samples of three composite bone repair scaffolds with different material ratios after stretching. The polycaprolactone scaffold will deform and be continuously stretched after being subjected to a small force. The polycaprolactone + nano-hydroxyapatite and polycaprolactone + nano-hydroxyapatite + nano-magnesium oxide composite bone repair scaffolds can withstand greater tension, and the fracture surface does not deform and breaks directly.

[0022] Furthermore, hydroxyapatite is partially degraded and releases calcium ions when it degrades. The bone repair process is actually a process of cell reconstruction. The material most needed by cells during the reconstruction process is calcium. Hydroxyapatite releases calcium ions inside the defect area, and cells use calcium ions for bone repair.

[0023] Furthermore, during the degradation of the composite bone repair scaffold, the decomposition of polycaprolactone is divided into two stages: First, polycaprolactone undergoes hydrolysis and cleavage of ester bonds in the human body, causing its molecular weight to gradually decrease, but at this stage, its quality does not decrease significantly; Secondly, when the molecular weight drops below 5000, the material breaks down into fragments and begins to lose weight; at the same time, most of the degradation products of polycaprolactone are absorbed and digested by human cells, while the parts that cannot be absorbed are excreted from the body through the excretory system.

[0024] Furthermore, during the degradation of the composite bone repair scaffold, the degradation rate of nano-magnesium oxide is affected by the pH value. Under different pH conditions, the solubility and reactivity of nano-magnesium oxide are different: Under acidic conditions, the solubility of nano-magnesium oxide increases because nano-magnesium oxide reacts with hydrogen ions to generate magnesium ions and water; this reaction promotes the degradation of nano-magnesium oxide because the surface of nano-magnesium oxide is corroded by acidic substances, accelerating its dissolution process; Carbon dioxide and water are produced during the degradation of polycaprolactone, and further reaction will generate carbonic acid, thereby slightly reducing the pH value of the bone defect. The reduced pH value will accelerate the hydrolysis of nano-magnesium oxide, further accelerating the release of magnesium ions at the bone defect site; ultimately, the composite bone repair scaffold achieves the function of continuous quantitative release of magnesium ions. Magnesium ions have the function of promoting the maturation of osteoblasts and preventing their death in the human body, and can also promote the proliferation and differentiation of bone marrow stromal stem cells into osteoblasts. The continuous release of a small amount of magnesium ions is beneficial to the repair of bone tissue.

[0025] Furthermore, magnesium ions produced by the degradation of nano-magnesium oxide activate the PI3K / Akt signaling pathway in mammalian cells. The PI3K / Akt signaling pathway is ubiquitous in mammalian cells and is responsible for regulating cell growth, differentiation and death. Appropriate concentrations of magnesium ions (6-10 millimolar) can activate this signaling pathway, thereby enhancing the adhesion ability, vitality, alkaline phosphatase (ALP) activity, mineralization of the extracellular matrix, and expression levels of genes related to osteoblast differentiation.

[0026] Furthermore, the bone repair material can also prevent and control orthopedic inflammation. When inflammatory symptoms appear at the bone defect site, the surrounding pH value will drop significantly. A lower pH value can allow the composite bone repair scaffold printed by the bone repair material to release a large amount of magnesium ions in a short period of time, thereby playing an anti-inflammatory role.

[0027] like Figure 6 As shown, Figure 6 It is the surface micromorphology of the composite bone repair scaffold. There are many protrusions and depressions on the surface of the composite bone repair scaffold, the surface roughness is low, and nano-hydroxyapatite crystals and nano-magnesium oxide crystals can be observed overflowing on the surface, which is conducive to cell adhesion and surface proliferation.

[0028] like Figure 7 As shown, Figure 7 It is the cross-sectional microscopic morphology of the composite bone repair scaffold. There are many nano-hydroxyapatite crystal clusters and nano-magnesium oxide crystal clusters in the cross-sectional area of ​​the composite bone repair scaffold. The presence of the crystal clusters greatly improves the strength of the composite bone repair scaffold. The degradation process is similar to the release of magnesium ion microspheres, which continuously release magnesium ions during degradation.

[0029] like Figure 8 As shown, Figure 8 This is a degradation experiment of a composite material bone repair scaffold. The degradation rate was slow in the first 10 days. As time went by, the degradation rate continued to increase, and after one month, it degraded by 24.2%. According to this rate, the composite material bone repair scaffold disclosed in the present invention can be completely degraded within 4 months, which meets the requirement of complete degradation before the repair of human bone tissue is completed.

[0030] like Fig. 9 As shown, Fig. 9 The magnesium ion release curve of the composite bone repair scaffold at a pH value of 7.4. The scaffold was immersed in PBS, and the PBS solution was changed daily. The PBS after the scaffold was immersed was taken every day to detect the magnesium ion concentration. It was found that no matter how many days of immersion, the release of magnesium ions was always constant between 8 and 9 mM. This concentration can promote bone tissue repair. It is proved that the bone repair scaffold disclosed in the present invention has a pH controlled release effect and can quantitatively release magnesium ions.

[0031] like Fig.10 As shown, Fig.10 This is the magnesium ion release curve of the bone repair scaffold immersed in a simulated body fluid with a pH value of 6. On the fifth day, the solution was changed back to a PBS solution with a pH value of 7.4. In the first four days, the release of magnesium ions in the simulated inflammatory environment was high, and the concentration in the solution could reach 15~16mM. After the pH value increased from the fifth day, the magnesium ion release tended to be normal, and the concentration returned to 8~9mM. This shows that the release amount of the bone repair scaffold can be regulated by the pH value.

[0032] like Fig.11 As shown, Fig.11 This is a microscopic image of the composite bone repair scaffold 10 days after biomineralization. A thick layer of calcium salt is deposited on the surface of the bone repair scaffold, indicating that the bone repair scaffold has excellent bone-forming ability.

[0033] Embodiment 3, a method for preparing a bone repair material based on pH controlled release, the method for preparing the bone repair material comprises the following steps: S1. Mixing bone repair materials by melting method: adding quantitatively weighed polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide into a polytetrafluoroethylene beaker, heating and dissolving the composite material in an oil bath, and setting the temperature of the oil bath to 150-160°C; S2. After melting for 30 to 40 minutes, take out the polytetrafluoroethylene beaker, stir the materials with a polytetrafluoroethylene stirring rod to fully mix them, stir for 5 to 10 minutes, and then heat them in an oil bath again. Repeat the above steps 4 to 6 times. After multiple melting and stirring, polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide are fully mixed. S3. Fill the evenly mixed composite bone repair material into a barrel, install the barrel into a pneumatic fused deposition biological 3D printer, and use the biological 3D printer to print a criss-cross composite bone repair scaffold.

[0034] By controlling the pH value to continuously and quantitatively release magnesium ions, when osteoarthritis or bone tissue inflammation occurs at the bone defect site due to improper surgery or rejection reaction, the composite bone repair scaffold releases magnesium ions faster, which has an anti-inflammatory effect, and the continuously released magnesium ions can promote bone tissue repair; the composite scaffold will slowly degrade after implantation into the human body, and when the bone tissue has fully grown, the composite bone repair scaffold will also be almost completely degraded, and the degradation product is hydroxyapatite that already exists in the human skeleton; no secondary surgery is required, reducing the patient's pain, and it has better bone repair performance than traditional bone repair scaffolds.

[0035] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0036] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A bone repair material based on pH controlled release, wherein the raw materials constituting the bone repair material include polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide; characterized in that: The raw materials of the bone repair material are calculated by weight: 5-10 parts of polycaprolactone, 5-10 parts of nano-hydroxyapatite, and 40-80 parts of nano-magnesium oxide; The bone repair material is printed with a criss-cross composite bone repair scaffold by 3D printing technology, and the decomposition and release rate of the composite bone repair scaffold is controlled based on the pH value.

2. The bone repair material based on pH controlled release according to claim 1, characterized in that: The composite bone repair scaffold prepared by printing the bone repair material continuously degrades in the human body, and the degradation products of the composite bone repair scaffold include water, carbon dioxide and hydroxyapatite.

3. The bone repair material based on pH controlled release according to claim 2, characterized in that: The hydroxyapatite is partially degraded, and calcium ions are released when the hydroxyapatite is degraded.

4. The bone repair material based on pH controlled release according to claim 3, characterized in that: During the degradation process of the composite bone repair scaffold, the decomposition of polycaprolactone is divided into two stages: First, polycaprolactone undergoes hydrolysis and cleavage of ester bonds in the human body, causing its molecular weight to gradually decrease, but at this stage, its quality does not decrease significantly; Secondly, when the molecular weight drops below 5000, the material breaks down into fragments and begins to lose weight; at the same time, most of the degradation products of polycaprolactone are absorbed and digested by human cells, while the parts that cannot be absorbed are excreted from the body through the excretory system.

5. The bone repair material based on pH controlled release according to claim 4, characterized in that: During the degradation process of the composite bone repair scaffold, the degradation rate of nano-magnesium oxide is affected by the pH value. Under different pH conditions, the solubility and reactivity of nano-magnesium oxide are different: Under acidic conditions, the solubility of nano-magnesium oxide increases because nano-magnesium oxide reacts with hydrogen ions to generate magnesium ions and water; this reaction promotes the degradation of nano-magnesium oxide because the surface of nano-magnesium oxide is corroded by acidic substances, accelerating its dissolution process; During the degradation process of polycaprolactone, carbon dioxide and water are produced, and further reaction will generate carbonic acid, thereby slightly reducing the pH value of the bone defect. The reduced pH value will accelerate the hydrolysis of nano-magnesium oxide, further accelerating the release of magnesium ions in the bone defect.

6. The bone repair material based on pH controlled release according to claim 5, characterized in that: The magnesium ions generated by the degradation of the nano-magnesium oxide activate the PI3K / Akt signaling pathway in mammalian cells.

7. The bone repair material based on pH controlled release according to claim 1, characterized in that: The bone repair material can also prevent and control orthopedic inflammation.

8. A method for preparing a bone repair material based on pH controlled release, comprising the bone repair material according to any one of claims 1 to 7, characterized in that: The preparation method of the bone repair material comprises the following steps: S1. Mixing bone repair materials by melting method: adding quantitatively weighed polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide into a polytetrafluoroethylene beaker, heating and dissolving the composite material in an oil bath, and setting the temperature of the oil bath to 150-160°C; S2. After melting for 30 to 40 minutes, take out the polytetrafluoroethylene beaker, stir the materials with a polytetrafluoroethylene stirring rod to fully mix them, stir for 5 to 10 minutes, and then heat them in an oil bath again. Repeat the above steps 4 to 6 times. After multiple melting and stirring, polycaprolactone, nano-hydroxyapatite and nano-magnesium oxide are fully mixed. S3. Fill the evenly mixed composite bone repair material into a barrel, install the barrel into a pneumatic fused deposition biological 3D printer, and use the biological 3D printer to print a criss-cross composite bone repair scaffold.

Citation Information

Patent Citations

  • Bone repair material and preparation method and application thereof

    CN113694254A

Cited By

  • Calcium phosphate-polycaprolactone composite scaffold and preparation method and application thereof

    CN122351600A

  • A polycaprolactone composite stent and a preparation method and application thereof

    CN122786564A